Musical.Ly’s Sleight of Hand: Circumventing Family Social Media Governance - Savic, Milovan; McCosker, Anthony (AoIR Selected Papers of Internet Research, 2017)
The prominence of mobile devices and social media in the lives of preteen children has grown dramatically over the recent years. Handheld devices make young people’s engagement with networked publics more flexible, frequent and personalised. However, this development also introduces new challenges for parents in their efforts to govern child’s online practices. Parental uncertainties with the digital environment are further intensified by the dominating fear discourse in public discussions. As a result, parents often develop more restrictive practices towards children’s social media use. Flipped expertise around new platforms, such as Musical.ly, where young people might be more proficient than their parents, further problematise parental governing practices. In this paper, we will discuss how young people negotiate networked publics and social media use within the family context. This negotiation happens on two level as young people need to simultaneously negotiate platform affordances and parental restrictions. We argue that young people engage with Musical.ly in _publicly private_ and _privately public_ manner; In doing so, they, in fact, manipulate media to achieve independence and create meaningful online spaces for engagement and interaction.